The Effect of Doppler Phenomenon on the Speed of Blood Flow - Khalid, Ghaidaa Abdulrahman (Al-Khwarizmi Engineering Journal, 2012)
This research studying the phenomenon of Doppler (frequency Doppler) as a method through which the direction and speed of the blood cells flows in blood vessels wear measured. This Doppler frequency is relied upon in medicine for measuring the speed of blood flow, because the blood flow is an important concept from the concepts of medicine. It represents the function and efficient of the heart and blood vessels in the body so any defect in this function will appear as a change in the speed of blood flow from the normal value assumed. As this speed changes alot in cases of  disease and morbidity  of the heart, so in order to identify the effect of changing the Doppler frequency on the speed of blood flow and the relationship of this frequency with the angles of transitions and receptions and the effect of changing the ultrasound transmitted frequencies on the measured velocities .The Doppler ultrasound system has been used which is more efficient and easier to be widely used as a practical application in Al Yarmouk Teaching Hospital on two subjects. The normal had a natural medical history in the blood vessels, and abnormal had carotid artery stenosis. This device will give the flow velocity of blood  in the blood vessels which is useful to the examiner, the equation of Doppler as a mathematical model in the research is adopted the measured speed to clarify the amount of change in the frequency (shift in frequency). This speed was measured in five different blood vessels, large arteries (abdominal aorta and carotid artery in the neck) and large veins (the inferior vena cava across the abdomen and the external Jugular vein in the neck) and capillaries in the hand and fingers. Then using the measured velocities in these vessels the Doppler frequency was calculated from this mathematical model using MATLAB program, was found that as velocity of the blood increases, so does the Doppler frequency and vice versa. The greater the value of the Doppler angle used in the device then the Doppler frequency decreased and vice versa. As well as increasing the transmitted frequency giving an  increase in the speed of blood flow and in the Doppler frequency and vice versa. It was observed during the practical work that it was possible to get the speed of blood flow in different blood vessels, arteries and veins easily, but to less extent in the capillary vessels since in fact the value of the received frequency was very small.